Prevention of stunting in school children through the utilization of local food in the form of tamban fish (Spratelloides gracilis) and spinach at Rugemuk Village Labu beach district - Nasution, Ernawati; Sudayarti, Erti; Ardiani, Fitri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Tamban fish and spinach are one type of food that is beneficial to health. Aside from being a staple food, tamban fish have good nutritional content such as protein, fat, calcium, phosphorus, iron, vitamin A, vitamin B1 and vitamin C. Meanwhile, spinach contains fiber and antioxidants that are high enough to meet the body's needs. However, processed food based on tamban fish and spinach leaves until now is still lacking due to lack of consuming tamban fish because it has a lot of thorns and consumes less spinach because it doesn't like eating vegetables. So in this service, another method is introduced for the utilization of these two foodstuffs by processing them into meatballs from tamban fish and spinach in fulfilling nutritional intake, especially in children in preventing stunting. The method used in this training is counseling and practice which includes providing material with lectures through face to face, dialogue and questions and answers and discussion. The training that has been carried out provides understanding and skills to the people of the Rugemuk Village in Pantai Labu Subdistrict, in the use of tamban fish and spinach that are processed into fish flour as ingredients for making meatballs which are functional food, participants' responses when providing training and material about the content nutrition in tamban and spinach leaves and their use in other forms is quite positive. The participants were very enthusiastic during the training as seen from the many participants who asked. And the practice of making meatballs from tamban fish flour and spinach leaves carried out also succeeded in increasing the knowledge and skills of the participants in regards to processing tamban fish and spinach leaves. It is hoped that the active role of the participants in disseminating information about the use of tamban fish and spinach leaves which can be processed into fish meal as ingredients in making meatballs to other communities in their surroundings.